Brain Perfusion Impairment in Neurologically Asymptomatic Adult Patients with Sickle-Cell Disease Shown by Voxel-Based Analysis of SPECT Images - Deus-Silva, Leonardo; Bonilha, Leonardo; Damasceno, Benito P.; Costa, Andre L.; Yasuda, Clarissa L.; Costa, Fernando F.; Santos, Allan O.; Etchebehere, Elba; Oquendo-Nogueira, Regis; de Freitas, Claudio F.; Camargo, Edwaldo E.; Min, Li L.; et al. (Frontiers in Neurology, 2013)
Cerebrovascular lesions are frequently observed in patients with sickle cell disease (SCD) and these structural lesions are preceded by insidious perfusion deficits. Our aim was to investigate the presence of brain perfusion deficits in neurologically asymptomatic SCD patients, especially affecting microvessels. For this study, forty-two SCD patients (33 sickle cell anemia (HbSS), 6 sickle hemoglobin C disease (HbSC) and 3 sickle β-thalassemia disease (HbSβ) with mean hematocrit of 25.1 (±4.85; 15.6-38.5) underwent brain perfusion SPECT using the tracer 99mTc-ECD. Images from SCD patients were compared to images of a healthy control group (29 females and 20 males, mean age 31 ±8; range 25-49 years). Images underwent voxel-wise comparison of regional tracer uptake using paired t-test to estimate the probability of each voxel to have an increased or decreased tracer uptake. When compared to controls, SCD patients exhibited significantly reduced tracer uptake in basal ganglia and thalami, the anterior frontal region and the watershed region of the temporo-parietal-occipital transition. (p<0.05). Our study showed that neurologically asymptomatic adult SCD patients exhibit a pattern of reduced 99mTc-ECD tracer uptake demonstrated by SPECT. Early diagnosis of this cerebral vasculopathy has prognostic implications and can be determinant in considering therapeutic alternatives to avoid increasing brain lesion load and progressive disability.